Persepsi Pelaku UMKM tentang Dampak Media Sosial dalam Pengembangan Bisnis - Dinda Maharani Putri; Rizky Hidayat Maulana; Farhan Bagas Saputra (Economics Note, 2025)
This study aims to analyze the perceptions of Micro, Small, and Medium Enterprises (MSMEs) regarding the impact of social media on the development of their businesses. Social media has become a highly influential platform for the marketing of products and services, enabling MSME actors to reach a wider market at relatively low cost. The method used in this study is a survey combined with in-depth interviews with MSME actors in several regions to explore their views on the use of social media as a tool for marketing and business development. The findings indicate that most MSME actors perceive social media as having a positive impact, such as increased visibility, network expansion, and higher sales. However, there are also challenges related to limited human resources and technical skills in managing social media effectively. This study concludes that social media plays a significant role in supporting MSME business growth, although some obstacles still need to be addressed in order to maximize its impact. Therefore, further training and support are required for MSME actors in leveraging social media for their business development.